Association of Phase Angle with Exercise Performance in Adolescent Female Basketball Players - Shiose, Keisuke; Yamamoto, Taiki; Hide, Taijiro; Tanoue, Yukiya; Tomiga-Takae, Rie; Yamashita, Atsuya; Michishita, Ryoma; Higaki, Yasuki; Uehara, Yoshinari (International Journal of Sports Medicine, 2025)
The phase angle measured by bioelectrical impedance analysis is a potential indicator of exercise performance. Owing to the lack of studies on adolescent female athletes, this study aimed to investigate the relationship between whole-body and regional phase angles and exercise performance in adolescent female basketball players. Forty-five female basketball players (aged 16.6±0.6 y) participated in this study. Lean soft tissue and phase angles for the whole-body, upper limb, and lower limb were assessed using the bioelectrical impedance analysis method. Participants performed maximal isometric knee extension and flexion strength, 20-m sprint, a vertical jump, an agility T-test, and a 20-m shuttle run test. The phase angle for the whole-body and the phase angle for the upper limb, but not the phase angle for the lower limb, were significantly correlated with the 20-m sprint and endurance capacity (all p<0.01). Even after adjusting for age and lean soft tissue in multiple regression analysis, the phase angle for the whole-body and the phase angle for the upper limb remained a significant predictor of these parameters (all p<0.05). The phase angle for the upper limb, combined with age and lean soft tissue, explained endurance capacity similarly to the phase angle for the whole-body (adjusted R2: 0.24 vs. 0.23) but was better for the 20-m sprint (adjusted R2: 0.26 vs. 0.11). Both whole-body and regional phase angles are associated with sprint and aerobic performance in adolescent female basketball players. However, the regional phase angle can be an equivalent or superior predictor of these performance parameters compared with the whole-body phase angle.
Keywords: bioelectrical impedance; female; basketball; phase angle